Into the large ears: otitis externa associated with nematodes, mites, and bacteria in Asian elephants (Elephas maximus) - Marcos Antonio Bezerra-Santos; Jairo Alfonso Mendoza-Roldan; Peter M. DiGeronimo; Erica Ward; Bruce Noden; Francesca De Luca; Elena Fanelli; Domenico Valenzano; Riccardo Paolo Lia; Domenico Otranto (Parasites & Vectors, 2023)
Abstract Background The Asian elephant (Elephas maximus), which is an endangered species, harbors several parasites. Among the ectoparasites that it harbors, ear mites of the genus Loxanoetus have the potential to cause external otitis, an inflammation that may also be associated with the presence of other microorganisms. We assessed the relationships between ear mites, nematodes, yeast, bacterial rods, and cocci sampled from the ears of captive Asian elephants in Thailand. In addition, we discuss the possibility that dust-bathing behavior may be triggered by ear mite infestation, and that this in turn may lead to contamination of the ears with soil microorganisms. Methods Legally owned captive Asian elephants (n = 64) were sampled. Ear swabs were individually collected from both ears and microscopically examined for the presence of mites, nematodes, yeast, bacterial rods, cocci, and host cells. Mites and nematodes were identified to species level using morphological and molecular methods. Results Loxanoetus lenae mites were present in 43.8% (n = 28/64) of the animals (19 animals with mites in one ear and nine animals with mites in both ears). Nematodes of the genus Panagrolaimus were detected in 23.4% (n = 15/64) of the animals (10 with nematodes in one ear and five with nematodes in both ears). In adult elephants (Fisher’s exact test, P = 0.0278) and female elephants (Fisher’s exact test, P = 0.0107), the presence of nematodes in both ears was significantly associated with the presence of mites. In addition, higher categorical burdens of nematodes were also significantly associated with the presence of mites (Fisher’s exact test, P = 0.0234) and epithelial cells (Fisher’s exact test, P = 0.0108), and marginally significantly associated with bacterial cocci (Fisher’s exact test, P = 0.0499). Conclusions The presence of L. lenae mites in the ear canals of the Asian elephants was significantly associated with the occurrence of other microorganisms, such as soil nematodes, bacteria and yeasts. The presence of mites in their ears may increase the dust-bathing behavior of elephants which, if confirmed, represents a further paradigmatic example of a parasitic infestation affecting animal behavior. Graphical Abstract